Role of ambulatory blood pressure monitoring in elderly hypertensive patients - Miguel Camafort; Wook-Jin Chung; Jin-Ho Shin (BMC, 2022)
Abstract Background Arterial hypertension is facing some changes in the last years. Its prevalence is increasing in elderly subjects. This growing prevalence is due to longer survival of the population worldwide, among other factors. On the other hand, recent guidelines have insisted in the relevance of out of office blood pressure measurements, to improve diagnostic and management of hypertension. Therefore, elderly subjects with hypertension could benefit from out of office blood pressure measurements, like ambulatory blood pressure measurements; nevertheless, there are very few or no specific recommendations regarding this. Aim In this review, we will gather the most important information about this subject. Results As hypertension in the elderly has some specific characteristics related to aging of the cardiovascular system, the most important aspect could be that these characteristics make ambulatory blood pressure measurement suitable for its use in elderly. Among those a higher prevalence of white coat hypertension, white coat phenomenon, and a higher nocturnal blood pressure and higher prevalence of nondipper and riser pattern, represent aspects that should be considered for better diagnostic and an improved management. Conclusion As the prevalence of hypertension will grow in the next years, more studies specifically directed to this subject are needed.